2019
DOI: 10.1155/2019/3164043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents and Stabilizer Molar Ratio on the Growth Orientation of Sol-Gel-Derived ZnO Thin Films

Abstract: This work targets to control the growth orientation of sol-gel-derived ZnO thin films in order to allow different modes of excitation (longitudinal and transverse) when targeted to be used in piezoelectric applications. For that, the effect of solvents and stabilizer molar ratio on the structural and optical characteristics of the obtained films is investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Vis spectrophotometry. The XRD results show clearly that the synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The absorbance spectrum of ZnO nanorods with isopropanol resulted in higher absorption than methoxy. The results of this work are in accordance with the research that has been done previously which proves that isopropanol has been shown to act as an appropriate solvent to control the growth orientation of ZnO thin films due to its suitable structural and optical properties [17]. The presence of isopropanol grows a larger area of rods and thus potentially results in higher absorbance levels.…”
Section: The Optical Properties Of Zno Nanorodssupporting
confidence: 90%
See 1 more Smart Citation
“…The absorbance spectrum of ZnO nanorods with isopropanol resulted in higher absorption than methoxy. The results of this work are in accordance with the research that has been done previously which proves that isopropanol has been shown to act as an appropriate solvent to control the growth orientation of ZnO thin films due to its suitable structural and optical properties [17]. The presence of isopropanol grows a larger area of rods and thus potentially results in higher absorbance levels.…”
Section: The Optical Properties Of Zno Nanorodssupporting
confidence: 90%
“…Based on previous research, it is known that isopropanol as a solvent or seed solution has more stable properties because it acts as a proton donor [19]. Previous research results have confirmed that the ZnO thin film preference growth axis indicates that the isopropanol is the best one [17]. This proves that the size of the diameter and absorbance at the photoanode which is influenced by a good seed solution will affect the performance of DSSCs.…”
Section: The Photovoltaic Performance Of Dsscs Based Zno Nanorodsmentioning
confidence: 84%
“…The relative intensity ratio of I (002) of ZnO synthesized on Zn-HMTA seed layer is 0.92, which is significantly improved compared to that reported by [40] and [41]. On the other hand, Figure 5 shows the XRD pattern of ZnO nanostructures synthesized on Zn-Pandan seed layer at temperatures of 100, 200, 300, 400, and 500 It was found out that the (100) peak is dominant compared to (002) suggesting the formation of rod-like shape of nanoparticles is dominant compared to highly dense nanorods [36].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 53%
“…Finally high temperature sintering is applied to the membrane to optimize mechanical properties and pore structure [8,89]. In order to make homogeneous membranes with less defects, colloidal particles are dispersed uniformly in the solvent by stabilizers such as nitric acid, ethanolamine (MEA) and triethylenetetramine (TETA) [104,105,106]. Since complex fabrication process of multi-layered membranes as well as expensive precursor materials indicating high manufacturing cost, simplified synthesis method and use of cheap materials will reduce the production cost and accelerate the development and commercialization of ceramic membranes.…”
Section: Reverse Osmosis and Nanofiltration Membranesmentioning
confidence: 99%